2023
DOI: 10.1364/josab.489223
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a multipartite hybrid quantum system with beamsplitter, dipole–dipole, and Ising interactions

Abstract: The possibility of exploiting heterogeneous quantum systems to high precision, for storing, processing, and transmitting information, makes them ideal candidates for multitasking purposes in quantum communication. Appropriate quantum systems involving a judicious choice of interactions that augment each other are potentially useful for probing deep into quantum regimes. Here, we use one such hybrid bipartite quantum model, with one subsystem made of a pair of qubits and another comprising a pair of oscillators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…So, from this analysis it can be concluded that the addition of squeezing in the system creates entanglement in atom A-field a, field a-field b subsystems and also entanglement gets transferred from atom-atom subsystem to other subsystems. In [45] and in [50], it is observed that if the field is in a coherent state, every subsystems suffers ESDs and duration of these ESDs get increased with increasing coherent photons. While, in these cases, entanglement get transferred from one subsystem to another, however, increase in coherent photons does not create new entanglement.…”
Section: For Bell Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…So, from this analysis it can be concluded that the addition of squeezing in the system creates entanglement in atom A-field a, field a-field b subsystems and also entanglement gets transferred from atom-atom subsystem to other subsystems. In [45] and in [50], it is observed that if the field is in a coherent state, every subsystems suffers ESDs and duration of these ESDs get increased with increasing coherent photons. While, in these cases, entanglement get transferred from one subsystem to another, however, increase in coherent photons does not create new entanglement.…”
Section: For Bell Statesmentioning
confidence: 99%
“…The entanglement dynamics of DJCM with Ising-type interaction when the field mode is either a coherent state or a thermal state is investigated in [50]. In our work, we consider a field mode which is either a squeezed coherent state or a Glauber Lachs state and do not use any approximation which consequently captures the entire dynamics of the entanglement.…”
Section: Entanglement Dynamics With Ising Interactionsmentioning
confidence: 99%